Evaluating Patterns and Outcomes in the Prescription of Incremental Peritoneal Dialysis in Support of Shared Decision-Making - Jessica Selwood; Rishana Shuaib; Ted J. FitzGerald; Sally Punzalan; Gaetano Lucisano; Edwina A. Brown; Richard W. Corbett (Clinical Journal of the American Society of Nephrology, 2026)
Introduction: Incremental peritoneal dialysis (PD), where ‘less than full-dose’ prescriptions are increased as residual kidney function declines, contributes to increased quality of life and reduced dialysis burden. Evidence supporting the safety of incremental regimens and informing patient expectations is limited. This study examined time to increment in dialysis prescriptions, PD modality transfer, transfer to haemodialysis and mortality rates within a single centre delivering incremental PD. Methods: Patients incident to PD and on incremental regimens were followed for changes in prescription, modality transfer and death between January 1, 2012 and December 31, 2023. Multivariable Cox regression assessed factors associated with time to increment, and Kaplan–Meier methods with log-rank testing were used for time-to-event analyses. Results: The cohort included 527 patients. At one year, 64% (95% CI 60-69%) remained on the same starting regimen, with 36% of people (95% CI 31-41%) having not incremented by two years. Time to increment was shorter for younger age at PD start (per decade, HR 0.92, 95% CI 0.85-0.99, P=0.02), male sex (HR 1.67, 95% CI 1.29-2.16, P